Endocrinology - Hadley, Mac E;Ed. Levine, Jon E;Ed (Pearson Prentice Hall, 2007)
This edition offers clear and authoritative explanations of basic concepts, interesting examples and applications, and detailed coverage of vertebrate hormones. A particular focus is placed on the critical roles of glands, hormones, receptors, and molecular signaling pathways in the control of physiological processes.